Rhodium "PONOP" pincer complexes for amine-borane dehydrogenation - Spearing-Ewyn, EAK (2020)
This thesis explores the reactivity of the {Rh(PONOP)}+ fragment with the tertiary amine-borane, H3B·NMe3, and the secondary amine-borane, H3B·NMe2H, with an overall aim of gaining mechanistic insight into the transition metal-catalysed dehydrocoupling of amine-boranes.